Intimacy and Modernity. Modernization of Love in the Western Culture - Musiał, Maciej (Poznańskie Towarzystwo Przyjaciół Nauk, 2013)
The aim of this paper is to confront two different accounts of contemporary trans formations of intimacy. The first account, represented mainly by Anthony Giddens and Brian McNair, concentrates on processes of democratization and emancipation; simply speaking, this approach suggests that modern intimacy contains higher amount of freedom than the pre-modern one. The second account emphasizes significance of processes of commercialization and rationalization of intimacy; according to this approach intimacy becomes more and more dependent to the capitalistic market. This point of view is represented by social scientists like Ulrich Beck, Elisabeth Beck-Gernsheim, Eva Illouz and Arlie Russell Hochschild. The aim of the article is to analyze abovementioned accounts not as opposite, but as complementary perspectives, which enables to notice highly ambivalent character of modernization of intimacy and modernization in general.
Keywords: intimacy; pure relationship; commercialization; colonization; rationalization; modernization